Japanese and Chinese Immigrant Activists - Fowler, Josephine (Rutgers University Press, 2021)
Japanese and Chinese immigrants in the United States have traditionally been characterized as hard workers who are hesitant to involve themselves in labor disputes or radical activism. How then does one explain the labor and Communist organizations in the Asian immigrant communities that existed from coast to coast between 1919 and 1933? Their organizers and members have been, until now, largely absent from the history of the American Communist movement. Here, Josephine Fowler brings us the first in-depth account of Japanese and Chinese immigrant radicalism inside the United States and across the Pacific.